A flexible exception handling framework for Semantic Programming Language - Zhao, Kai; Zhang, Linlin; Ying, Shi (2011 International Conference on Mechatronic Science, Electric Engineering and Computer, 2011)
Semantic Web services (SWS) and business process management (BPM) technologies are gradually applied in many domains like electronic commerce and enterprise application integration, which has unavoidably led to the requirements and concerns for effectively recovering from kinds of failures, especially in complex, untamed and dynamic Web environments. Generally, Exception handling is considered to be one of the most important mechanisms for dealing with exception conditions. However, current business process programming languages for semantic Web services provide almost no support for exception handling, and support platforms are weak in providing reliability and adaptability. In this paper, we present a novel framework for flexible exception handling and fault recovery of semantic business processes based on Semantic Programming Language (SPL). Especially, the framework provides forward recovery support with dynamically discovering and substituting failed services when an exception arises during execution by semantically equivalent or semantically similar Web services.